2011
DOI: 10.1007/s12272-011-0817-5
|View full text |Cite
|
Sign up to set email alerts
|

Induction of apoptotic cell death by ursolic acid through mitochondrial death pathway and extrinsic death receptor pathway in MDA-MB-231 cells

Abstract: Ursolic acid (3-hydroxy-urs-12-en-28-oic acid) is a pentacyclic triterpenoid derived from leaves, berries, fruits, and flowers of medicinal plants, such as Rosemarinus officinalis. Ursolic acid has been shown to inhibit tumorigenesis, tumor promotion, and suppress angiogenesis. In our present study, we found that ursolic acid decreased cell proliferation rate and induce apoptosis in human breast cancer cell line, MDA-MB-231. When we checked the expression levels of proteins associated with apoptosis signal by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
71
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(72 citation statements)
references
References 48 publications
0
71
0
1
Order By: Relevance
“…Caspases are essential proteins for the execution of cell death induced by apoptotic stimuli (Kim et al, 2011). The activity of proteolytic caspase-9 and downstream effector caspase-3 promoted subsequent cellular destruction.…”
Section: Discussionmentioning
confidence: 99%
“…Caspases are essential proteins for the execution of cell death induced by apoptotic stimuli (Kim et al, 2011). The activity of proteolytic caspase-9 and downstream effector caspase-3 promoted subsequent cellular destruction.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that the LCR extract improves insulin resistance and lipid metabolism in obesediabetic rats (10). Since it has been known that LCR contains a variety of physiologically active compounds such as apigenin, luteolin, kaempferol, quercetin, oleanolic acid, and urosolic acid (11,12) which may have anticancer activities (13)(14)(15), LCR may exert an inhibitory effect on tumor growth. However, little information is available regarding the effect of LCR on cancer cell growth.…”
Section: Introductionmentioning
confidence: 99%
“…9 Ursolic acid (UA), a natural pentacyclic triterpenoid carboxylic acid, is a potent anticancer agent. It has been shown to prevent tumorigenesis, inhibit tumor growth 10,11 and suppress angiogenesis. 12 UA was shown to sensitize cancer cells to chemotherapeutic agents, to induce cancer cell apoptosis and to inhibit the growth of DU145 cells in nude mice.…”
mentioning
confidence: 99%